Communicative internet-practices in forming socio-cultural values of the society - Денисюк, Ж. З. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The role is studied of communicative Internet practices in the transformation of the axiological sphere of society. On the basis of the analysis of the specifics of Internet communication, its influence on the formation of modern socio-cultural values has been identified.